THE IMPLEMENTATION OF THE GOVERNMENT SYSTEM IN INDONESIA DURING THE REFORMATION ERA ACCORDING TO 1945 CONSTITUTION - Wahyono, Eko (Sekolah Tinggi Ilmu Syariah Wal Aqidah Ash-Shofa Manonjaya, 2025)
The purpose of this research is to deeply examine and analyze the implementation of the government system during the reformation era based on the 1945 Constitution. As stated in fourth paragraph of the Preamble of the 1945 Constitution, the National Independence of Indonesia is composed in a Constitution of the State of Indonesia which is structured in a form of Republic of Indonesia, governed with people sovereignty. The sovereignty of the people is the highest power and it determines the leaders in the Indonesian government. This is confirmed in Article 1 paragraph (2) of the 1945 Constitution. The subject regarding the government is stated in Article 1 paragraph (1) of the 1945 Constitution; Indonesia is a unitary state in the form of a republic. Based on these facts, it can be concluded that the form of the Indonesian state is unitary, while the form of government is a republic. The President of the Republic of Indonesia holds the power as the head of state and the head of government, as stated in Article 4 paragraph (1) that